Rho GTPase activating protein 11A promotes tongue squamous cell carcinoma proliferation and is a transcriptional target of forkhead box M1 - Weiwei Zhang; Xueyan Bai; Tingting Liu; Yulong Mao; Lingnan Zhang; Wenlong Wang; Huanying Yu (Elsevier, 2024)
Background/purpose: Rho GTPase activating protein 11A (ARHGAP11A) can facilitate GTP hydrolysis in RhoA. The functions of ARHGAP11A in oral squamous cell carcinoma (OSCC) have not yet been explored. This study aimed to investigate the expression profile of ARHGAP11A in OSCC, its correlation with patient prognosis, its effect on cell-cycle progression, and the mechanisms by which it is dysregulated. Materials and methods: Bioinformatics analysis was conducted using data from The Cancer Genome Atlas-Head and Neck Squamous Cell Carcinoma (TCGA-HNSC). Lentiviruses carrying ARHGAP11A shRNAs were employed to determine the effects of ARHGAP11A knockdown on tumor cell proliferation and cell-cycle progression. Dual-luciferase reporter assays were utilized to examine how FOXM1 transcriptionally regulates ARHGAP11A expression. Results: ARHGAP11A upregulation was associated with unfavorable overall survival (OS) in patients with TSCC (HR: 2.142, 95%CI: 1.224-3.749, P = 0.007), but not in patients with OSCC of sites other than the tongue. ARHGAP11A knockdown inhibited the proliferation of TSCC cells in vitro and in vivo, and induced G1 phase arrest. ARHGAP11A knockdown increased GTP-RhoA but decreased p-RB levels, while it did not affect the total expression of RhoA and RB. ARHGAP11A knockdown increased p27 and decreased cyclin E1 expression. ARHGAP11A is transcriptionally activated by FOXM1 via multiple FOXM1 binding sites in the promoter regions in TSCC cells. Conclusion: This study revealed the oncogenic role of ARHGAP11A in TSCC, highlighting its impact on cell-cycle control and tumor proliferation. Furthermore, the regulatory relationship between FOXM1 and ARHGAP11A provides new insights into the transcriptional networks in TSCC.